2017
DOI: 10.1140/epje/i2017-11508-6
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced structural and thermodynamic phase transitions in micellar systems

Abstract: In this contribution a methodology to compute and classify shear-induced structural and phase transitions in surfactant/water mixtures from rheological measurements is presented. Non-linear rheological experiments, considering variations in surfactant concentration and temperature, are analyzed. In particular, the parameters of the BMP (Bautista-Manero-Puig) model, obtained from the fitting of the shear stress versus shear rate data, which are functions of surfactant concentration and temperature, allow classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…46,47 The strong shear force can induce the extension of the micelles and cause orientation along the shear direction. 48,49 It is assumed that the C8 micelles are gradually deformed, extended, ruptured, and aligned along the direction of movement caused by the strong shear force. In this way, the viscosity in shear direction becomes much lower than that perpendicular to it and the system becomes anisotropic.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,47 The strong shear force can induce the extension of the micelles and cause orientation along the shear direction. 48,49 It is assumed that the C8 micelles are gradually deformed, extended, ruptured, and aligned along the direction of movement caused by the strong shear force. In this way, the viscosity in shear direction becomes much lower than that perpendicular to it and the system becomes anisotropic.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The measurement of the lubricant film thickness in the friction gap and the determination of the shear rate at different mechanical loads show that the high shear rate in such samples leads to low friction (Figure ). Nilsson and He have reported that C8 micelles are present in solution in the form of a spherical-capped cylinder. , The strong shear force can induce the extension of the micelles and cause orientation along the shear direction. , It is assumed that the C8 micelles are gradually deformed, extended, ruptured, and aligned along the direction of movement caused by the strong shear force. In this way, the viscosity in shear direction becomes much lower than that perpendicular to it and the system becomes anisotropic.…”
Section: Discussionmentioning
confidence: 99%